2018
DOI: 10.5177/ntvt.2018.05.17192
|View full text |Cite
|
Sign up to set email alerts
|

Real patients in virtual reality: the link between phantom heads and clinical dentistry

Abstract: Preclinical training in phantom heads has until now been considered the 'gold standard' for restorative dental education, but the transition from preclinic to the treatment of real patients has remained a challenge. With the introduction of the latest generation of virtual reality simulators, students and dental practitioners can make digital impressions of their patients in virtual reality models and practice procedures in virtual reality before clinically performing them. In this way, clinical decisions can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…These findings are also consistent with those of another study, which demonstrated that when VR was used to explain the theoretical knowledge and skills underlying the imaging of mandibular lesions to dentistry students, the theoretical test scores and average OSCE score of the VR education group were higher than those of the traditional education group [12]. Using VR in clinical dentistry was also reported to be able to enhance students' self-confidence [31] and improve their attitudes toward patients [9]. In other RCT studies, VR-based educational interventions have been reported to exhibit learning outcomes similar to traditional education techniques [32][33][34].…”
Section: Discussionsupporting
confidence: 89%
“…These findings are also consistent with those of another study, which demonstrated that when VR was used to explain the theoretical knowledge and skills underlying the imaging of mandibular lesions to dentistry students, the theoretical test scores and average OSCE score of the VR education group were higher than those of the traditional education group [12]. Using VR in clinical dentistry was also reported to be able to enhance students' self-confidence [31] and improve their attitudes toward patients [9]. In other RCT studies, VR-based educational interventions have been reported to exhibit learning outcomes similar to traditional education techniques [32][33][34].…”
Section: Discussionsupporting
confidence: 89%
“…Other research provided evidence that students can improve their tooth extraction skills [93], dental radiology skills [47], and implant skills [32,90] through dental simulators. Dental simulators were also reported to be able to enhance students' confidence [94] and improve their attitudes toward patients [53] and abilities to discern and solve medical emergencies [70,95,96]. Some studies focused on students' acceptance of dental simulators and found that most students are willing to learn with dental simulators, which would boost their enthusiasm to learn [97].…”
Section: Effectiveness Of Dental Simulatorsmentioning
confidence: 99%
“…The development of manual and cognitive skills during the training of future dentists has always been facilitated by the use and learning of therapeutic manoeuvres using traditional simulators, such as acrylic artificial dental fillings, extracted teeth, or phantom heads, the last invented in 1930 by Oswald Fergus [64] and known as "the gold standard in restorative dentistry" [65] for the satisfactory replication of the real oral environment, the positioning of the dentist in relation to the patient during the performance of different dental procedures. Consequently, the acquisition of practical skills by dental students through the exclusive use of traditional simulators was the topic for Q15 in our survey.…”
Section: Discussionmentioning
confidence: 99%